Risperidone Induced Benign Intracranial Hypertension Leading to Visual Loss - Alexander, Sushil Thomas (Indian J Psychol Med, 2016)
Benign intracranial hypertension (BIH) is a rare but potentially serious condition causing visual loss. Occasionally, medication use has been associated with the occurrence of BIH. We report the case of a 40-year-old obese lady being treated with risperidone for schizophrenia who presented with features of BIH. We report this case, occurring for the 1(st) time in India, to emphasize that a commonly used atypical antipsychotic drug can rarely cause BIH leading to visual loss.